15-Deoxy-Delta-12,14-Prostaglandin J2 Inhibits Lung Inflammation and Remodeling in Distinct Murine Models of Asthma - Coutinho, Diego S.; Anjos-Valotta, Edna A.; do Nascimento, Caio V. M. F.; Pires, Ana Lucia A.; Napimoga, Marcelo H.; Carvalho, Vinícius F.; Torres, Rafael C.; e Silva, Patrícia M. R.; Martins, Marco A. (Frontiers in Immunology, 2017)
15-deoxy-Δ-12,14-prostaglandin J2 (15d-PGJ2) has been described as an anti-inflammatory lipid mediator in several in vitro and in vivo studies, but its effect on allergic pulmonary inflammation remains elusive. The aim of this study was to investigate the therapeutic potential of 15d-PGJ2 based on distinct murine models of allergic asthma triggered by either ovalbumin (OVA) or house dust mite extract (HDM). Characteristics of airway inflammation, hyperreactivity (AHR), mucus exacerbation and lung remodeling in sensitized A/J mice treated or not with 15d-PGJ2 were assessed. 15d-PGJ2 treatments were carried out systemically or topically given via subcutaneous injection or intranasal instillation, respectively. Analyzes were carried out 24 h after the last allergen provocation. Irrespective of the route of administration, 15d-PGJ2 significantly inhibited the peribronchial accumulation of eosinophils and neutrophils, subepithelial fibrosis and also mucus exacerbation caused by either OVA or HDM challenge. The protective effect of 15d-PGJ2 occurred in parallel with inhibition of allergen-induced AHR and lung tissue production of pro-inflammatory cytokines, such as IL-5, IL-13, IL-17 and TNF-α. Finally,15d-PGJ2 was found effective in inhibiting NF-kB phosphorylation upon HDM challenge as measured by Western blotting. In conclusion, our findings suggest that 15d-PGJ2 can reduce crucial features of asthma, including AHR, lung inﬂammation and remodeling in distinct murine models of the disease. These effects are associated with a decrease in lung tissue generation of pro-inﬂammatory cytokines by a mechanism related to down-regulation of NF-κB phosphorylation.